When vowels make us smile: The influence of articulatory feedback in judgments of warmth and competence - Garrido, M. V. (2021)
In six studies (N=725), we extended the articulatory feedback hypothesis to person perception, examining how words featuring /i:/ sounds that activate the zygomaticus major muscle and words featuring /u:/ sounds activating the orbicularis oris muscle affect preference, warmth, and competence judgments of mock-usernames. Users with usernames including /i:/, in contrast to /u:/ sounds, were always preferred and judged as warmer and more competent. The impact of this manipulation in shaping preference as well as judgments on the core dimensions of social perception confirms the stability of the vowel-emotion link and the role of articulatory feedback in social information processing.